Innovations in Pedagogical Didactics of Teaching Physics to University Students - Jalilova, Sevinj; Anna Babchenko (Universitas Negeri Semarang, 2024)
The relevance of the study lies in the lack of information about the current processes in understanding and applying innovative practices of teaching physics in the current conditions of systematic transformation of professional education. In the context of the main purpose of teaching and the need to improve the quality of educational services offered, considering interdisciplinary advances in the fields of science, we consider it timely to conduct an additional study of the potential and limitations of didactics of pedagogical science from the position of multifactorial influence of universal informatization, transforming the nature of interactions at various levels. This study aims to identify teachers' views on the opportunities and risks of innovation, as well as to establish the range of pedagogical tools they use to improve students' learning in physics. To this end, a non-experimental quantitative design was used, involving the collection of information through a questionnaire completed by 24 physics teachers in an interview survey, providing additional questions in the context of the research objective. In obtaining the results, the rules of analysis and validity criteria of the data recorded in the protocols were followed, through the procedure of measuring the level of agreement between the interviewer by category and checking the reliability of the analyzed data. The results show the possibilities of effective application of innovations by teachers in the process of teaching physics, the study and systematization of which can further improve the quality of educational services and competitiveness of specialists.